Pengaruh Penggunaan Soil Stabilization Terhadap Sifat Fisik Beton Dengan Agregat Halus Berkadar Lumpur Tinggi - Siregar, Syarif Hidayat; Ismeddiyanto, Ismeddiyanto; Djauhari, Zulfikar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This study examines the physical properties of concrete with high mud fine aggregate by adding soil stabilization. Based on SNI 03-2461-2002, it is stated that fine aggregate should not contain mud more than 5% of the weight. Soil stabilization as addition material in the mortar mixtures could increase the quality of concrete. This research aims to identify the influence of soil stabilization material to the performance of concrete that was the addition mixed with the fine aggregate that contain high percentage. The percentage of mud used in this study were 0%, 5%, 10%, 15%, 20% and 23% of the fine aggregate weight. Percentage of soil stabilization was 1% from concrete’s mud weight. The designed strength of concrete was 20 MPa. All samples were cured by soaking them in normal water for 28 days. The concrete physical properties observed in this study consisted of workability, sorptivity, and porosity. The results of the tests showd that the compressive strength of concrete with 20% variation mud level and added soil stabilization was 30,41% higher compared to concrete without soil stabilization. Sorptivity results in 5% of mud variation with the addition of soil stabilization had the lowest absorption of 16,10% lower than absorption compared to 10% sludge variation. Porosity values in 5% mud variation with the addition of soil stabilization have the smallest porosity of 15.81% lower compared to other mud variations. Based on the results of these tests it could be concluded that the strength of high mud concrete by adding soil stabilization was better than without soil stabilization. Keywords : Physical properties, sorptivity, tensile strength, porosity, soil stabilization, mud